STEROIDS IN THE TREATMENT OF CHRONIC DISEASES - SHARMA P; IMAM S; MEHTA DK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Since their identification, which was almost 80 years ago, steroids have played a prominent role in the treatment of many disease states such as chronic obstructive pulmonary disease, asthma, rheumatoid arthritis, and inflammatory bowel disease. Many of the clinical roles of steroids are related to their potent anti-inflammatory and immune-modulating properties. Numerous skin diseases are successfully treated with systemic steroids. Corticosteroids, though they are lifesaving drugs, produce adverse reactions which may be mild or life threatening. Steroids have diverse effects on various systems of the body. Therefore, educational interventions among physician, patients, as well as students should be carried out to further enhance rational drug use. The purpose of this review was to identify the most commonly prescribed steroids and their side effects, basic pharmacology, complications, as well as the assessment of patient knowledge about the use of steroids in tertiary care teaching hospitals.